Assessing quality of life of kidney donors in Tehran in 2012-2013 - Haghighi, hadis; Shiri, hossein; Borzabadi Farahani, ziba; Alavi Majd, hamid; Dabirian, azam; Zareaee, ehsan (Advances in Nursing & Midwifery, 2015)
Background and aim: Kidney transplantation is the best treatment for patients with end stage renal disease. Living donor kidney transplantation is increasingly performed in Iran. Since the quality of life of live kidney donors has been subjected to little investigation, the present study was conducted to investigate the quality of life of live kidney donors in Tehran in 2012-2013. Materials and methods: This is a descriptive study conducted on 45 donors living in Tehran in 2012- 2013. Sample selection was started by recruiting convenient samples following by snow ball sampling. Data were collected by a questionnaire consisting of as a three sections: demographic information, SF-36 quality of life questionnaire and researcher made questionnaire .The data were analyzed by SPSS 19 . Results: Mean age of the donors was 34/4 year. 62/2 % of the donors were men. The quality of life of 66/7 % of donors in physical, 60 % in mental and 48/9 % in social domain were classified as moderate (score:34-66). The mean score of quality of life of donors was 59. 59.58 % of the participants donated their kidney for financial reasons and there was no significant correlation between the quality of life scores and reason for donation. 31 % of the donors regretted the donation.68/8% of donors do not encourage donation and recommend it to others and the average score of these donors is less than the donors who recommend donation(p <0/001) Conclusion: The quality of life of kidney donors in this study was moderate. It is worthwhile to follow up the donors and to assess physical and mental problem of donors after donation in order to reduce subjective outcomes and regret in donors. There is a need for financial support of kidney donors. Key words: Quality of life , Kidney donation, Live donor